UTILITY OF NEPHROSONOGRAM PRIOR TO ISOTOPE RENOGRAPHY - Taher, M. A. (The ASEAN Journal of Radiology, 2023)
The purpose of the present paper was to determine if nephrosonogram is useful prior to radionuclide renogram. METHODS : 752 renograms (464 males, 288 females, age range 18 months to 77 years) were done, amongst these prior ultasound scans were performed in 612 patients. Additional imaging tests e.g. [VU, renal angiogram etc. were done in 88 cases only. RESULTS : Significant increases in the accuracy of renogram were observed with prior ultrasound scan. We performed nephrosonography almost routinely prior to radionuclide renogram by probe renograph or gamma camera using I-131 hippuran orthoiodohippurate (OIH) or Tc 99m diethylene triamine pentaacetate (DTPA). The 1st or arterial phase may be missed in probe renograph if the renal hilum is not marked by ultrasound. Recently gamma cameras are available in our country and probe renograph is almost obsolete. Therefore nephrosonogram may not be so essential to study individual renal function. However, in some gamma cameras, one or more photomultiplier tube (PMT) may be out of order and useful field size may be limited. In these situations prior nephrosonogram may be helpful in optimization of quality of gamma camera renogram also. All the Nuclear Medicine Centres in Bangladesh are equipped with Ultrasonographs and no extra charge is made for nephrosonogram prior to radionuclide renogram. CONCLUSIONS : We recommend USG prior to renogram. Renal hilum os easily marked by ultrasounf scan and during nephrosonography (USG), some other important findings e.g. renal size, shape, position, number, calculus, cyst, neoplasm etc. also can be visualized. Intravenous Urography (IVU) and digital subtraction angiography (DSA) are rarely needed*.